2020
DOI: 10.1101/2020.05.03.20089557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Coronavirus Disease 2019 (COVID-19) on Liver Injury in China: A Systematic Review and Meta-analysis

Abstract: made critical revisions to the manuscript. Conflict of Interest StatementNo conflicting relationship exists for any of the authors. AcknowledgmentsThanks for prof. Zehua Lei revising the manuscrip Abbreviations:Abstract Background: The evidence for the incidence and severity of liver injury in Chinese patients with COVID-19 is still

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…Currently, the pathological impact of COVID-19 on the liver is still largely unknown. 19 , 20 In our current study, we found that 51.7% of patients on admission had abnormal liver function. Previous investigations have proposed that COVID-19 triggers hepatic injury by inducing viral hepatitis.…”
Section: Discussionsupporting
confidence: 48%
“…Currently, the pathological impact of COVID-19 on the liver is still largely unknown. 19 , 20 In our current study, we found that 51.7% of patients on admission had abnormal liver function. Previous investigations have proposed that COVID-19 triggers hepatic injury by inducing viral hepatitis.…”
Section: Discussionsupporting
confidence: 48%
“…2 3 Most patients with COVID-19 have dyspnoea as the main clinical manifestation, and some cases may be complicated by heart, kidney, circulatory, liver, nerve and other multisystem injuries. [4][5][6][7][8] These patients may eventually die of diffuse alveolar injury and progressive respiratory failure. The cytokine storm syndrome involved in the pathogenesis of acute respiratory distress syndrome and organ failure during SARS-CoV infection seems to be related to a massive inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%
“…19 infection compared to patients with milder symptoms (OR 2.07) (7). However, severe liver injury, defined as ALT or AST >3-fold or g-GT, ALP and bilirubin >2-fold above normal, during COVID-19 rarely occurs (10)(11)(12).…”
Section: Accepted Manuscriptmentioning
confidence: 99%